Challenges and Opportunities for Immunoprofiling Using a Spatial High-Plex Technology: The NanoString GeoMx® Digital Spatial Profiler - Hernandez, Sharia; Lazcano, Rossana; Serrano, Alejandra; Powell, Steven; Kostousov, Larissa; Mehta, Jay; Khan, Khaja; Lu, Wei; Solis, Luisa M. (Frontiers in Oncology, 2022)
Characterization of the tumor microenvironment trough immuno-profiling has become an essential resource for the understanding of the complex immune cell interactions, and assessment of biomarkers for prognosis and prediction of immunotherapy response, however these studies are often limited by tissue heterogeneity and sample size. The nanoString GeoMx® Digital Spatial Profiler (DSP) is a platform which allows high-plex profiling at protein and RNA level, providing spatial and temporal assessment of tumors in frozen or formalin-fixed paraffin-embedded limited tissue sample. Recently, high impact studies have shown the feasibility to use this technology to identify biomarkers in different settings, including predictive biomarkers for immunotherapy in different tumor types. These studies showed that compared to other multiplex and high-plex platforms, the DSP can interrogate higher number of biomarker with higher throughput, however, it does not provide single cell resolution, including co-expression of biomarker or spatial information at single cell level. In this review we will describe a technical overview of the platform, current evidence of the advantages and limitations of the applications of this technology, and we will provide important considerations for the experimental design for translational immune-oncology research using this tissue-based hi-plex profiling approach.